Production of Analog Rice From Composite Flour : Mocaf, Corn, and Porang Flour - Florie, Ghiffara Amanda; Kusumayanti, Heny (Journal of Vocational Studies on Applied Research, 2024)
Rice is a primary food that commonly consumed by people in Indonesia and even in Asia. Apart from rice, Indonesia actually has various kinds of plants that can be used as a primary foods such as corn, cassava, sweet potatoes, sago, etc., but are still rarely consumed by the public. Analog rice can be an alternative so that Indonesian people can consume non-rice primary foods with a similar texture to rice. In this research, analog rice was made from raw material such as cassava, corn and porang tubers. The aim of this research is to produce analog rice from a mixture of mocaf, corn flour and porang flour and determine public acceptance of analog rice products based on organoleptic tests. The production of analog rice consists of several processes such as preparing raw materials, mixing, steaming, extrusion process and drying the analog rice. Based on research, it was found that F1 and F5 formulation were the best analog rice based on organoleptic tests, and F5 formulation was the closest to IR64 rice based on proximate tests.